Comparative Analysis of Lightning Properties of Selected GTL based Dielectric Liquids under Positive Lightning Impulse - Stuchala, Filip; Rozga, Pawel (Electrical Insulation Conference and Electrical Manufacturing Expo, 2023)
This article presents the results of studies on the lightning impulse breakdown characteristics of comprehensive range of insulating liquids from the same manufacturer. The insulating liquids made with the innovative GTL technology thanks to which they contain very little sulphur and have high resistance to oxidation were tested. These insulating fluids were compared with classic mineral oils. A synthetic ester was also tested. For all mentioned liquids lightning impulse breakdown voltage and acceleration voltage at positive polarity were compared. Measurements were made in the point-to-sphere electrode system for a 25 mm gap. The results show comparable values of breakdown voltage independently of the liquid considered. However, in terms of acceleration voltage ester behaves worse in relation to GTL fluids and mineral oils. In turn, when comparing GTL fluids, inhibited and gas absorbing GTL (GTL-I-GA) is characterized by the highest values of breakdown voltage as well as acceleration voltage.